Making History Visible: Ireland's National Famine Way Told Through Models and Interactive Digital Narratives - Quinn, E. Moore (The international journal of religious tourism and pilgrimage, 2022)
The National Famine Way is a trail along Ireland’s Royal Canal that traces the remarkable trek of the 1,490 tenants who were evicted by their landlord, Denis Mahon, from his estate in Strokestown, County Roscommon, in the Republic of Ireland, during ‘Black ’47,’ the worst year of the Great Irish Famine (Irish: An Gorta Mór, the Great Hunger of 1847). The evictees were ‘escorted’ from their homes to vessels that awaited them in Dublin. They were then taken to Liverpool, where they were placed on four so-called ‘coffin ships’ bound for Canada. The path along the Royal Canal is 165 kilometres, or approximately one hundred miles. Today it is shared by hikers, bikers, ‘boat people,’ site-seekers, commemorators, and self-identified famine ‘pilgrims.’ For some of the latter, the signposts of children’s shoes erected along the path have acquired an iconic or even mythic significance. This article begins by applying a model that approaches the Way as a five-pronged cultural heritage complex. The article expands the model by considering how the National Famine Way’s cultural heritage is being approached from the lenses of transmedia.